'Black diamonds', 'clever blacks' and other metaphors: Constructing the black middle class in contemporary South African print media. Issue 2 (April 2018) - Dimitris Kitis, E; Milani, Tommaso M; Levon, Erez
South Africa (SA) has been undergoing a process of transformation since the end of White minority rule (apartheid) in 1994. During this period, various employment and lifestyle opportunities have given rise to a growing Black middle class (BMC). Against this backdrop, the article draws upon an intersectional approach to corpus-assisted discourse studies in order to examine the construction of the BMC in a 1.4 million-word corpus composed of 20 mainstream Anglophone South African newspaper titles published between 2008 and 2014. With the help of the corpus tool AntConc, the article investigates the collocates of 'black middle class', 'black diamonds', 'clever blacks' and 'coconuts', classifying results according to semantic categories in order to provide an idea of the multiple but nuanced representations of the BMC in contemporary SA. The analysis finds several lexically rich moralizing and paternalistic discourses that, in accordance with an intersectional perspective, enact a complex pattern of strategies that are simultaneously exclusionary and inclusionary.